2016
DOI: 10.3732/ajb.1600134
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome number reduction in the sister clade of Carica papaya with concomitant genome size doubling

Abstract: On the basis of outgroup comparison, 2n = 18 is the ancestral number, and repeated chromosomal fusions with simultaneous genome size increase as a result of repetitive elements accumulating near centromeres characterize the papaya clade. These results have implications for ongoing genome assemblies in Caricaceae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 49 publications
(61 reference statements)
1
19
0
Order By: Relevance
“…in Brassicaceae [ 53 ]), it has been found that they could vary considerably and change rapidly in other families (e.g. in Caricaceae, Turneraceae, Poaceae, Arecaceae; [ 56 , 57 , 58 , 59 , 60 ]. Moreover, species with the lowest chromosome number, based on descending dysploidy, could have genomes that are twice as large as those of their closest relatives [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…in Brassicaceae [ 53 ]), it has been found that they could vary considerably and change rapidly in other families (e.g. in Caricaceae, Turneraceae, Poaceae, Arecaceae; [ 56 , 57 , 58 , 59 , 60 ]. Moreover, species with the lowest chromosome number, based on descending dysploidy, could have genomes that are twice as large as those of their closest relatives [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…in Caricaceae, Turneraceae, Poaceae, Arecaceae; [ 56 , 57 , 58 , 59 , 60 ]. Moreover, species with the lowest chromosome number, based on descending dysploidy, could have genomes that are twice as large as those of their closest relatives [ 57 ]. C-value analyses in Phalaris [ 38 ] show that the x = 6 species have a significantly higher genome size than other diploids in the x = 7 group (see Fig 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromosome number information detects major genomic events such as aneuploidy and polyploidy and has been consistently investigated (Guerra, 2008;Rice et al, 2015). In plant systematics, cytotaxonomic, phylogenetic and speciation inferences of chromosome numbers have been appreciated throughout the vascular pant lineages (de Azkue and Martĩnez, 1990;Chung and Kim, 1997;McArthur and Sanderson, 1999;Windham and Yatskievych, 2003;Peruzzi et al, 2009;Rockinger et al, 2016).…”
mentioning
confidence: 99%
“…and tropical woody species (Bationo-Kando et al, 2016;Cai et al, 2013;Dahmer et al, 2009;Schneider et al, 2015). Traditional cytology can be used for identifying aneuploids (additional or missing chromosomes) (Hu et al, 2015) or dysploids (alterations from chromosome fusion or fission) difficult to detect using flow cytometry (Rockinger et al, 2016). To meet the demand for accurate chromosome counts, traditional cytology has proven useful in the development of databases across taxonomic groups and formation of data sets for meta-analysis of chromosome number across plants and animals (Peruzzi et al, 2014).…”
mentioning
confidence: 99%